The Competent Pastor: Skills and Self-Knowledge for Serving Well - Sisk, Ronald D., (Rowman & Littlefield Publishers, 2005)
What does it mean to say that a pastor is competent? And how does a competent pastor function? This book is intended to help pastors, seminarians, and lay people who work with pastors understand and answer these two questions. Competence in ministry is a moving target. A ministry technique that works in one parish may not work in another. What works today may not work five years from now. But a competent pastor will be able to adapt to changing locations and changing times. A competent pastor will be happy in her job—or able to figure out why she’s not happy and how to move forward. A competent pastor won’t get stuck—or when he does get stuck, he’ll know what steps to take to get unstuck. Competence, defined by author Ronald Sisk as "the ability to do what needs to be done," requires ministers to understand themselves and others and to keep a realistic perspective on their lives. Competent pastors function by moving toward this kind of understanding and perspective.